IMPLEMENTASI PEMBELAJARAN MATERI PAI DI HOMESCHOOLING KAK SETO SURAKARTA : Pembelajaran PAI di Homeschooling Kak Seto - Syarifah; Morinda, Aura Folia; Yusuf, M. Dahril (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2022)
Academic learning patterns, the deprivation of children's creativity, inappropriate curriculum, and uninnovative learning methods are some of the issues that plague formal schools. Due to the numerous issues that arise in formal schools, most parents send their children to non-formal educational institutions.This paper talk about implementation of Islamic education at the Kak Seto's homeschool at Surakarta Solo and the motivations of the family for completing education there.The descriptive approach is used in this qualitative study.The specialist obtained the subject's perceptions during interviews conducted without the creator present, as well as documentation information from organizations, as sources for the research data.The first step in data analysis is data collection, which is followed by data presentation for drawing conclusions.According to the findings of this study, educational institutions for homeschoolers implement PAI learning materials in two sessions.Both classroom instruction and practice outside will be part of this session.Each students have a variety of past issues that force them to make significant learning adjustments.finally, the content of the PAI material is divided into various classes. the Parents choose this homeschooling for their children's education for a variety reasons, including bullying, broken homes, the work of parents who move frequently, and children with special needs.